PERAN KEPEMIMPINAN BATAK (Studi Eksplorasi pada Ganesha Operation Medan) - Sidabutar, Manganjur Marudut; Mas’ud, Fuad (Faculty of Economics and Business Diponegoro University, 2016)
This study aimed to know the role of Batak leadership style in the company, which waslead by Batak’s leader. The purpose of this research was to know the understanding and view of the owner of the company to Batak’s leadership. Starts from identifying leader and employee perception on the practice leadership based on the values in the Batak’s culture.Batak’s culture which was the root of the Batak society, had essential part in the character building of the leader in Indonesia. The practice leadership based on the value in the Bataks culture become an integral part in the Bataks leadership practice in company.This study uses qualitative methods in which data collection was the role of Bataks leadership. The sample in this study were workers who have work experience of minimal 5 years at Ganesha Operation Medan. Results obtained from this study states that of the three elements of Bataks culture those are somba Marula-ula, Elek Marboru and Manat Mardongan Tubu already reflects the role of Bataks culture in the Ganesha Operation Medan